On a matrix álgebra without matrices - Vera Saravia, Edgar (2019)
We enlarge a previus introduction to the two-dimensional geometric algebra published in Volume 05(02) of SELECCIONES MATEMÁTICAS. It is a friendly introduction of a theme of common interest for university proffessors and students of physics and mathematics.